MENDORONG PARTISIPASI PEMILIH MUDA MELALUI PENDIDIKAN POLITIK YANG PROGRAMATIK - Diyah Setiawaty (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2014)
Youth voters potential in Indonesia is quite large due to the significant number of voters. However, the potential of low level of political participation in society, especially among first-time voters are also predicted to increase with the increasing public apathy due to the poor performance of the elected government. Electoral education is a strategic mean to address these problems. Unfortunately since the beginning of the democratic election, after the new regime era, the Election Organizer (KPU) has not yet doing the electoral education and has been using the sameprogrammatic approach which isvoter information which only a temporary solution. Political parties also are still not up to running a electoral education functions as mandated by the law.It needs a mutual commitmentfrom the government and political parties to involve all elements of society such as CSO and educational institutions to start doing programmatic electoral/voter education to improve not only the rate of voter participation in elections but also the overall political participation.